Implementation of Contextual Teaching and Learning in the Formation of Student Discipline in Islamic Religious Education: A Case Study of Grade X Students at SMA Negeri 1 Kuala - Ulya, Syahri Fatul; Nurhasanah, Nurhasanah (The Islamic Education and Multiculturalism Foundation, 2026)
Abstrak Penelitian ini bertujuan mengeksplorasi implementasi model Contextual Teaching and Learning (CTL) dalam pembelajaran Pendidikan Agama Islam (PAI) serta menjelaskan bagaimana model tersebut mendukung pembentukan perilaku disiplin siswa. Penelitian menggunakan desain studi kasus kualitatif di kelas X SMA Negeri 1 Kuala. Informan terdiri atas 3 guru PAI dan 122 siswa kelas X yang dipilih secara purposif berdasarkan keterlibatan mereka dalam pembelajaran PAI dan relevansinya dengan fokus kedisiplinan. Data dikumpulkan melalui observasi kelas selama 8 kali wawancara semi-terstruktur, dan dokumentasi berupa catatan kehadiran, tugas, tata tertib kelas, serta dokumen pembelajaran. Data dianalisis melalui proses kondensasi data, penyajian data, dan penarikan/verifikasi kesimpulan. Temuan menunjukkan bahwa CTL diterapkan melalui pengaitan materi PAI dengan pengalaman keseharian siswa, diskusi kasus, kerja kelompok, pemodelan perilaku, refleksi nilai, dan penilaian autentik. Model ini mendukung pembentukan kedisiplinan melalui lima mekanisme pedagogis, yaitu relevansi pengalaman nyata, keterlibatan aktif siswa, kesadaran nilai, praktik tanggung jawab, dan pembiasaan perilaku. Studi ini tidak dimaksudkan untuk membuktikan pengaruh kausal CTL, melainkan menjelaskan proses pedagogis yang memungkinkan nilai disiplin diinternalisasi dalam pembelajaran PAI. Kata Kunci: Contextual Teaching and Learning; Kedisiplinan Siswa; Pendidikan Agama Islam; Pendidikan Karakter; Studi Kualitatif Abstract This study explores the implementation of Contextual Teaching and Learning (CTL) in Islamic Religious Education and explains how this model supports the formation of students’ disciplinary behavior. A qualitative case-study design was employed in grade X of SMA Negeri 1 Kuala. The participants consisted of 3 Islamic Religious Education teacher(s) and 122 grade-X students selected through purposive sampling based on their involvement in Islamic Religious Education learning and their relevance to the focus on discipline. Data were collected through classroom observations during 8, semi-structured interviews, and documentation, including attendance records, assignments, classroom rules, and learning documents. The data were analyzed through data condensation, data display, and conclusion drawing/verification. The findings indicate that CTL was implemented by connecting Islamic Religious Education materials with students’ daily experiences, case discussions, group work, behavioral modeling, value reflection, and authentic assessment. The model supports discipline formation through five pedagogical mechanisms: real-life relevance, active student engagement, value awareness, responsible practice, and behavioral habituation. Rather than claiming a causal effect, this study contributes to explaining the pedagogical process through which discipline values are internalized in Islamic Religious Education learning. Keywords: Contextual Teaching and Learning; Student Discipline; Islamic Religious Education; Character Education; Qualitative Study